PENGARUH LATIHAN RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI PRIMER - Elsa D. Amaral (CHMK Applied Science Journal, 2018)
Hypertension is often called the silent killer or a silent killer because early symptoms such as asymptomatic, but can result in permanent damage to organs vital. Salah a non-pharmacological measures which can help lower blood pressure is mucle relaxation exercises progresif, adapun purpose of this study was to analyze the effect of progressive muscle relaxation exercises to decrease blood pressure in patients with primary hypertension in the clinic Sikumana Kupang City. This study uses the pre – experimental type research with the study design is done in the working area of puskesmas Sikumana kupang city. Sample of 40 respondents were selected with consecutive sampling technique. The result showed that a decline in blood pressure on the respondent. Wherein prior to progressive muscle relaxation exercises most of the respondents had a blood pressure of hypertensive category thresholds and after progressive muscle relaxation exercises most of the respondents had a normal blood pressure categories. Conclusions of this study is a progressive muscle relaxation exercise effect to the decrease in blood pressure in patients with hypertension, based on the result of this study, suggested that progressive muscle relaxationexercises can be applied in the implementation of nursing care in patients with hypertension. Keywords: Blood pressure,hypertens,progressive relaxation mucle